Alternative Methods for Characterization of Extracellular Vesicles - Momen-Heravi, Fatemeh; Balaj, Leonora; Alian, Sara; Tigges, John; Toxavidis, Vasilis; Ericsson, Maria; Distel, Robert J.; Ivanov, Alexander R.; Skog, Johan; Kuo, Winston P. (Frontiers in Physiology, 2012)
Extracellular vesicles are nano-sized vesicles released by all cells in vitro as well as in vivo. Their role has been implicated mainly in cell-cell communication, but also in disease biomarkers and more recently in gene delivery. They represent a snapshot of the cell status at the moment of release and carry bioreactive macromolecules such as nucleic acids, proteins and lipids. A major limitation in this emerging new field is the availability/awareness of techniques to isolate and properly characterize Extracellular vesicles. The lack of gold standards makes comparing different studies very difficult and may potentially hinder some Extracellular vesicles -specific evidence. Characterization of Extracellular vesicles has also recently seen many advances with the use of Nanoparticle Tracking Analysis (NTA), flow cytometry, cryo-EM instruments and proteomic technologies. In this review, we discuss the latest developments in translational technologies involving characterization methods including the facts in their support and the challenges they face.